Room Acoustical Quality of Concert Halls: Perceptual Factors and Acoustic Criteria — Return from Experience. Issue 4 (December 2013) - Kahle, Eckhard
Several acousticians have attempted to define a complete set of factors describing room acoustic quality, based on laboratory and/or real hall listening tests. After finishing a PhD thesis on room acoustic quality, the author has worked on new constructions of performance spaces, renovations as well as optimizations of existing spaces and the question can now be asked whether the widely used set of objective criteria and perceptual factors proves sufficient to describe the problems and challenges encountered. When working on high-quality acoustic spaces, the commonly used set of acoustic criteria is insufficient to describe all aspects and problems. Further descriptors are required with respect to both acoustic measurements and perceptual factors. Proposals for additional acoustic criteria and their link to the architecture of a space will be given, aiming to better describe the signature of a room with respect to both source presence and room presence. The concept of "stream segregation" into source presence and room presence is confirmed, but for both the "source" and "room" parts not only the magnitude (strength) needs to be considered but equally more detailed aspects like "lateralness" and direction of arrival, i.e. what could be called the "spatial center of gravity". For example, changing the spatial center of gravity of the reverberation has very strong perceptual consequences. Another aspect that often tends to be neglected is the question of orchestral balance (for audience members but equally for musicians on stage) that can strongly be influenced by acoustic design decisions.